Therapeutic errors captured by the New Zealand National Poisons Centre: a retrospective audit - Rhiannon Braund; Desirée L. Kunac; Lucy M. Shieffelbien; Adam C. Pomerleau; Nicholas Y. Yang (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONMedication errors are one important cause of harm to patients. Information about medication errors can be obtained from diverse sources, including databases administered by poisons centres as part of their routine operation. AIMThe aim of this study was to describe the data regarding therapeutic errors captured by the New Zealand National Poisons Centre (NZNPC). METHODSA retrospective study of calls made to the NZNPC between 1 September 2016 and 31 August 2018 was conducted, which involved human patients and were classified as 'therapeutic error' in the NZNPC database. Variables extracted and analysed included the demographics of the individual, the substance(s) involved, and site of exposure. RESULTSDuring the study period, a total of 43,578 calls were received by the NZNPC, including 5708 (13%) that were classified as 'therapeutic error'. Just over half of the exposures occurred in females, 3197 (56%) and 4826 (85%) of the calls involved a single substance. All age groups were affected and 2074 (37%) of the calls were related to children aged <12 years. A residential environment (n=5568, 97%) was the site of exposure for almost all reported therapeutic errors, most commonly in the patient's own home (n=5207, 91%). DISCUSSIONThis study provides insights into therapeutic error-related calls to the NZNPC. Almost all errors occurred in the residential setting. Over one-third of the calls involved children. Enhanced data capture and classification methods are needed to determine the types of errors and their possible causes to better inform prevention efforts.